Intersubjectivity and transcendental theory of knowledge - López Molina, Antonio M. (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
This paper has a main objective: a reconstruction about the transcendental theory of knowledge in the philosophical experiences of Kant and Habermas. In respective works something similar happen, specifically structures of knowledge from Subjectivity to Intersubjetivity. In this way both authors break the Paradigm of Consciousness, and appear a specific communicative experience thought Sensus Communis, and Communicative Reason. This research focuses on the parallelism between two philosophical systems, whose foundation is the Enlightenment or the autonomy of reason. Transcendental Subjectivity, Sensus Communis, Knowledge and Human Interests, and Communicative Reason represent different solutions to the problem of communicability of the judgments through which declare the possibility, reality, and necessity of the states of affairs.